Genetic Relatedness of Staphylococcus haemolyticus in Gut and Skin of Preterm Neonates and Breast Milk of Their Mothers. Issue 3 (March 2019) - Soeorg, Hiie; Metsvaht, Hanna Kadri; Keränen, Evamaria Elisabet; Eelmäe, Imbi; Merila, Mirjam; Ilmoja, Mari-Liis; Metsvaht, Tuuli; Lutsar, Irja
Abstract : Background: Staphylococcus haemolyticus is a common colonizer and cause of late-onset sepsis (LOS) in preterm neonates. By describing genetic relatedness, we aimed to determine whether mother's breast milk (BM) is a source of S. haemolyticus colonizing neonatal gut and skin and/or causing LOS. Methods: S. haemolyticus was isolated from stool and skin swabs of 49 BM-fed preterm neonates admitted to neonatal intensive care unit, 20 healthy BM-fed term neonates and BM of mothers once a week and typed by multilocus variable number tandem repeat analysis and multilocus sequence typing. Virulence-related genes were determined by polymerase chain reaction. Results: Compared with term neonates, S . haemolyticus colonized more commonly gut (35% vs. 89.9%; P < 0.001) and skin (50% vs. 91.8%; P < 0.001) of preterm neonates and mothers' BM (15% vs. 38.8%). Isolates from preterm compared with term neonates and their mothers carried more commonly the mecA gene (83.5% vs. 5.4%; P < 0.001) and IS 256 (52.4% vs. 2.7%; P < 0.001) and belonged to clonal complex 29 (89.1% vs. 63%; P = 0.014). Only 7 (14.3%) preterm and 3 (15%) term neonates were colonized in gut or on skin with multilocus variable number tandem repeat analysis types indistinguishable from those in BM. Most frequent multilocus variable number tandem repeat analysis types belonged to sequence type 3 or 42, comprised 71.1%–78.4% of isolates from preterm neonates/mothers and caused all 7 LOS episodes. LOS-causing strain colonized the gut of 4/7 and the skin of 5/7 neonates, but not BM, before onset of LOS. Conclusions: S. haemolyticus colonizing gut and skin or causing LOS in preterm neonates rarely originate from BM but are mecA -positive strains adapted to hospital environment. Abstract : Supplemental Digital Content is available in the text.